Phosphorylated orange adsorption gel for removal of selected heavy metals - Tew, Seow Ting (2012)
Heavy metals pollution is the global problem which becomes a matter of great concern over last few decades. Automotive service and repair shops are one of the industrial which generate hazardous waste that harmful to public health and environment. This study is to determine the efficiency of bio-waste filter to remove the heavy metals and the efficiency between up-flow and gravity flow method in the treatment process. The phosphorylated orange adsorption gel (POAG) is chemically modified orange waste which consisted of orange peels and pulps. Besides cotton, glass beads, and glass filter, POAG is also part of the reactor for both up-flow and gravity flow method. The wastewater treatment is run for 7 hours time of interval. The wastewater samples are taken from the automotive service and repair shop at Gambang. The concentration of heavy metals and oil and grease of the samples are measured for each hour. From the data analysis, the average percentage removals of Copper using gravity flow and up-flow method are 94.12 % and 96.57 % respectively. The average percentage removals of Lead using gravity flow and up-flow method are 162.42 % and 188.51 % respectively. The average percentage removals of Nickel using gravity flow and up-flow method are 126.79 % and 139.29 % respectively. The average percentage removals of Zinc using gravity flow and up-flow method are 88.13 % and 88.44 % respectively. The average percentage removals of oil and grease using gravity flow and up-flow method are 99.02 % and 97.61 % respectively. Based on statistical analysis, both contact time and treatment methods are significant. By comparing the P-value of contact time and treatment methods, contact time is more significant than treatment methods because lower P-value of contact time. In conclusion, POAG has high ability to remove the heavy metals and oil and grease which contain in the samples. Up-flow method bas the higher efficiency for removing heavy metals compare to gravity flow method. For removal of oil and grease, gravity flow method possesses higher efficiency compare to up-flow method.